Reconsidering variation and change in the Medieval French subject system - Wolfe, S (Ubiquity Press, 2020)
This article draws on a novel corpus of medieval texts to explore diachronic change in the French subject system. It is argued that the relative frequency of null, preverbal and postverbal subjects is affected by changes in the syntax-information structure mapping during the medieval period, with the discourse value of both preverbal and postverbal subjects diachronically variable across the textual records. Furthermore, the discourse value of both so-called Germanic- and Romance- inversion structures is subject to change in the syntax-pragmatics mapping.